Improving Students’ Reading Skills through Speed Reading Assisted by Audio-Visual Media - Elda Rintan Parwati; Rian Nurizka (Postgraduate, University of Mataram, 2026)
This study aimed to improve the reading skills of third-grade students at SD Negeri Sonosewu through the application of the Speed-Reading method assisted by audio-visual media. The research was conducted during the first semester of the 2025/2026 academic year using Classroom Action Research (CAR) implemented in two cycles, each consisting of planning, action, observation, and reflection stages, with 27 students as participants. Data were collected through reading skill tests and classroom observations and analyzed using descriptive quantitative and qualitative techniques. The results showed that students' reading skills were initially low, with a pre-cycle average score of 52. After the implementation of the Speed-Reading method in Cycle I, the average score increased to 69, indicating sufficient improvement, although some students still experienced difficulties in understanding texts efficiently. Further improvements were applied in Cycle II, resulting in a significant increase in the average score to 85, which was categorized as very good and exceeded the success indicator of 75%. These findings indicate that the Speed Reading method assisted by audio-visual media is effective in improving the reading skills of third-grade students at SD Negeri Sonosewu.